The Length - Weight Relationship Factor and Sex-Ratio of Mantis Shrimp (Harpiosquilla spp) in Andaman Sea of Satun Province, Thailand - Samphan, P. ,; Ratanamusik, A. , (International Journal of Agricultural Technology, 2018)
This study estimated the length-weight relationship, sex ratio and population parameters of mantis shrimp, Harpiosquilla spp. from the coastal waters of Andaman Sea, Satun Province, Thailand between February 2015 and March 2016. The length- weight relationship factor of Mantis Shrimp in Andaman Sea of Satun Province, Thailand was conducted for 12 consecutive months (February, 2015 – March, 2016). Data were collected from 437 individuals. The research method was surveyed, descriptive analyzed and interviewed. The most frequently catch fish was shown between 190-335 mm. They was positive allometric pattern. Length - weight relationship had equation (all samples) W = 0.0341L 2.6564 (R² = 0.8129) and (males) W = 0.0257x2.7425 R² = 0.8377 and (females) W = 0.061x2.481 (R² = 0.7239). Mantis Shrimp sexual dimorphism with sex ratio of 1.54 : 1.0 which was significantly biased in favour of males. The catch mantis shrimp still had a chance to mature and spawn. However, the fishery aspects become important in this case and may need to investigate. The study provided a basic and valuable information for the Mantis Shrimp fisheries management and population monitoring.